Discriminant


The formula $x = \dfrac{-b \pm \sqrt{b^2-4ac}}{2a}$ gives the solutions to the general quadratic equation $ax^2+bx+c=0$. By examining the expression under the square root sign, $b^2-4ac$, we known as the discriminant, symbol used is $\Delta$.

The quadratic formula becomes $x=\dfrac{-b + \sqrt{\Delta}}{2a}$ and $x=\dfrac{-b – \sqrt{\Delta}}{2a}$.

$\Delta <0$
If $x^2+2x+3=0$, then $a=1,b=2$ and $c=3$.
\( \begin{align} \displaystyle
x &=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a} \\
&= \dfrac{-2 \pm \sqrt{-8}}{2}\\
\Delta &= b^2-4ac \\
&= 2^2-4 \times 1 \times 3 \\
&= -8 \\
\end{align} \)
If the discriminant is less than zero (negative), there are no real solutions because the expression under the square root sign is negative. It is not possible to find a real number which is the square root of a negative number.

$\Delta = 0$
If $x^2+8x+16=0$, then $a=1,b=8$ and $c=16$.
\( \begin{align} \displaystyle
x &=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a} \\
&= \dfrac{-8 \pm \sqrt{0}}{2}\\
&= -4 \\
\Delta &= b^2-4ac \\
&= 8^2-4 \times 1 \times 16 \\
&= 0 \\
\end{align} \)
If the discriminant is equal to zero then the two solutions are the same. This may be regarded as one rational solution that is equal to $ \displaystyle -\dfrac{b}{2a}$.
This is, if $b^2-4ac=0$, then $\displaystyle x=\dfrac{-b+\sqrt{0}}{2a}$ which is the same as $\displaystyle x=\dfrac{-b-\sqrt{0}}{2a}$.
One solution indicates that the quadratic trinomial is a perfect square that can be factorised easily using the perfect squares rule: that is $x^2+8x+16=(x+4)^2$.
We call this also as repeated or double root.

$\Delta > 0$
If the discriminant is positive there are two distinct solutions. We can determine more information than this by checking whether the discriminant is also a perfect square.
Case 1:
If $2x^2-7x-4=0$, then $a=2,b=-7$ and $c=-4$.
\( \begin{align} \displaystyle
x &=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a} \\
&= \dfrac{7 \pm \sqrt{81}}{2 \times 2}\\
&= \dfrac{7 \pm 9}{4} \\
&= 4 \text{ or } x=-\dfrac{1}{2}\\
\Delta &= b^2-4ac \\
&= (-7)^2 -4 \times 2 \times (-4) \\
&= 81 \\
\end{align} \)
If the discriminant is positive and a perfect square, the quadratic trinomial will have two rational solutions. This means the quadratic trinomial can be factorised easily; that is $2x^2-7x-4=(2x+1)(x-4)$.
Case 2:
If $x^2-5x-1=0$ then $a=1,b=-5$ and $c=-1$.
\( \begin{align} \displaystyle
x &=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a} \\
&= \dfrac{5 \pm \sqrt{29}}{2 \times 1}\\
&= \dfrac{5 \pm \sqrt{29}}{2}\\
\Delta &= b^2-4ac \\
&= (-5)^2 -4 \times 1 \times (-1) \\
&= 29 \\
\end{align} \)
If the discriminant is positive but not a perfect square, the factors are irrational and the quadratic formula is used to find the two irrational (surd) solutions.

Example 1

Use the discriminant to determine the nature of the roots of $2x^2-2x+5=0$.

\( \begin{align} \displaystyle
\Delta &= b^2-4ac \\
&= (-2)^2 -4 \times 2 \times 5 \\
&= -36 \\
\end{align} \)
Since $\Delta \lt 0$, there are no real roots.

Example 2

Use the discriminant to determine the nature of the roots of $3x^2-4x-2=0$.

\( \begin{align} \displaystyle
\Delta &= b^2-4ac \\
&= (-4)^2 -4 \times 3 \times (-2) \\
&= 40 \\
\end{align} \)
Since $\Delta \gt 0$, but $40$ is not a square, there are $2$ distinct irrational roots.

Example 3

Use the discriminant to determine the nature of the roots of $9x^2-6x+1=0$.

\( \begin{align} \displaystyle
\Delta &= b^2-4ac \\
&= (-6)^2 -4 \times 9 \times 1 \\
&= 0 \\
\end{align} \)
Since $\Delta = 0$, the equation has a repeated root.

Example 4

Find the values of $k$ for which $x^2-4x+k=0$ has 2 distinct real roots.

\( \begin{align} \displaystyle
\Delta &\gt 0 \\
b^2-4ac &\gt 0 \\
(-4)^2 -4 \times 1 \times k &\gt 0 \\
16 -4k &\gt 0\\
-4k &\gt -16 \\
\therefore k &\lt 4 \\
\end{align} \)

Example 5

Find the values of $k$ for which $kx^2+(k+3)x-1=0$ has real roots.

\( \begin{align} \displaystyle
\Delta &\ge 0 &\text{for real roots} \\
b^2-4ac &\ge 0 \\
(k+3)^2 -4 \times k \times (-1) &\ge 0 \\
k^2 + 6k + 9 + 4k &\ge 0\\
k^2 + 10k + 9 &\ge 0\\
(k+1)(k+9) &\ge 0 \\
\therefore k &\le -9 \text{ or } \ge -1 \\
\end{align} \)


Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorials Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Pythagoras Theorem Quadratic Quadratic Factorise Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Your email address will not be published. Required fields are marked *